Photoperiod preference of Indonesian leaffish (Pristolepis grooti) during post-transportation recovery period - Rupi Sanjaya; Ferdinand Hukama Taqwa; Mohamad Amin; Muhammad Nursan (Acta Aquatica: Aquatic Sciences Journal, 2026)
Photoperiod manipulation is one of the environmental management strategies that can influence the physiological condition of fish and support the success of aquaculture production. This study aimed to analyze the photoperiod preference of Indonesian leaffish (Pristolepis grooti) during the the post-transportation recovery period. The experiment used a Completely Randomized Design with three photoperiod treatments and three replications: (A) 24 hours light:0 hours dark (24L:0D), (B) 12 hours light:12 hours dark (12L:12D), and (C) 0 hours light:24 hours dark (0L:24D). The study was conducted at the Experimental Pond Instalation, Aquaculture Study Program, Universitas Sriwijaya. The results showed that treatment C (0L:24D) produced the lowest blood glucose level (93.33±2.08 mg dL⁻¹), the highest feed efficiency (1.67±0.05%), and relatively better absolute weight growth (0.05±0.01 g), with a survival rate reaching 93.33±11.55%. The oxygen consumption level indicated significant differences in metabolic activity among treatments, reflecting the best physiological condition of Indonesian leaffish under a 24-hour dark photoperiod (0.110±0.008 mg O2 g-1 h-1). Water quality values during the recovery period (temperature 28.1-30.2°C, pH 7.6-7.9, dissolved oxygen 2.9-3.1 mg L⁻¹, and ammonia 0.421-0,895 mg L⁻¹) were within the range that supports the survival of Indonesian leaffish. Treatment C (0L:24D) indicated the photoperiod preference of Indonesian leaffish during the post-transportation recovery period because it was able to maintain better physiological conditions, thereby supporting improved aquaculture performance during the subsequent culture period. Keywords: Feed Efficiency, Growth, Leaffish, Physiological Condition, Survival Rate, Photoperiod